Diseño eje urbano de protección, ronda humedal la Vaca sector Corabastos, Bogotá (2021)
The present work of degree of sectoral urban scope, consists of the design of the public space of the environmental corridor for the protection of the La Vaca wetland, through concepts of sustainability and landscape ecology. Located in the UPZ Corabastos, Kennedy locality, Bogotá. Proposal that seeks to increase the space effective public per inhabitant (DADEP, 2020), improving quality of life conditions of the population from the dimensions of environmental quality, well-being and identity, applying indicators of social, environmental and economic sustainability.